Circulating miRNA is a useful diagnostic biomarker for nonalcoholic steatohepatitis in nonalcoholic fatty liver disease - Tae Hyung Kim (Nature Portfolio, 2021)
Abstract Nonalcoholic steatohepatitis (NASH) is considered as a progressive form of nonalcoholic fatty liver disease (NAFLD). To distinguish NASH from nonalcoholic fatty liver (NAFL), we evaluated the diagnostic value of circulating miRNAs. Small RNA sequencing was performed on 12 NAFL patients and 12 NASH patients, and the miRNA expression was compared. After selecting miRNAs for the diagnosis of NASH, we analyzed the diagnostic accuracy of each miRNA and the combination of miRNAs. External validation was performed using quantitative reverse transcription PCR. Among the 2,588 miRNAs, 26 miRNAs significantly increased in the NASH group than in the NAFL group. Among the 26 elevated miRNAs in the NASH group, 8 miRNAs were selected, and in silico analysis was performed. Only four miRNAs (miR-21-5p, miR-151a-3p, miR-192-5p, and miR-4449) showed significant area under the receiver operating characteristic curve (AUC) values for NASH diagnosis. The combination of the four miRNAs showed satisfactory diagnostic accuracy for NASH (AUC 0.875; 95% CI 0.676–0.973). External validation revealed similar diagnostic accuracy for NASH (AUC 0.874; 95% CI 0.724–0.960). NASH represents significantly distinct miRNA expression profile compared with NAFL. The combination of serum circulating miRNAs can be used as a novel biomarker for the NASH diagnosis in NAFLD.